Reward and Punishment on Student's Motivation in Learning English at SMPN 2 Jujuhan Muara Bungo - Selly Indah Putri; M.Hairi Ihsan; Elmiati Elmiati (STKIP PGRI Sumatera Barat, 2023)
This study aims to determine the types of rewards and punishments used by teachers in learning English at SMPN 2 Jujuhan. The purpose of this research is to find information about what types of rewards and punishments are used by teachers. This research is a qualitative research with descriptive method. The participants in this study were one English teacher at SMPN 2 Jujuhan and students who received rewards and punishments from the teacher in the classroom. To collect data, researchers used instruments, namely observation checklists and interviews. Researchers obtained data on how the role of teachers in using the types of reward and punishment in the classroom, as well as conducting interviews with students who received rewards and punishments in the classroom as participants. Based on the data analysis, the researcher concluded that the English teacher at SMPN 2 Jujuhan used reward and punishment during English language learning. Of the 4 types of rewards and 2 types of punishment studied, the English teacher at SMPN 2 Jujuhan uses three types of rewards, namely: social rewards, token rewards, material rewards, while two types of punishment are used: presentation punishment, and removal punishment.